A new adaptation tracking tool will help countries capture climate adaptation actions in livestock systems - Wong, Madeline (CGIAR System Organization, 2022)
Agriculture is one of the sectors suffering the most. In East Africa alone, an estimated 8.9 million livestock have died this year from drought, impacting the food security and livelihoods of smallholder farmers and pastoralists. Successful climate adaptation by countries will require coordinated efforts across all sectors – from public to private – from national to international levels. It will also require financial support. Tracking adaptation efforts of countries, therefore, is a key priority and in response, the International Livestock Research Institute (ILRI) has developed a tool to track adaptation specifically in livestock systems.